Effect of Oral Mekobalamin on Peripheral Neuropathy in Leprosy Patients: A Pre–Post Clinical Study - Putu Evindya Vipascitadewi Nandanaya Bharata; Luh Made Mas Rusyati; Luh Putu Ratih Vibriyanti Karna; Nyoman Suryawati; IGN Darmaputra; Ni Made Dwi Puspawati (Universitas Muhammadiyah Malang, 2026)
Leprosy remains a significant public health problem in Indonesia, and peripheral neuropathy is a major cause of disability in affected patients. This study aimed to evaluate the effectiveness of oral mekobalamin in reducing neuropathic pain and improving peripheral sensory function in leprosy-related neuropathy. A pre-experimental one-group pre–post clinical study was conducted from March to May 2023 involving 31 adult leprosy patients. Participants received oral mekobalamin 500 micrograms every eight hours for 90 days. Neuropathic pain was assessed using the Douleur Neuropathique-4 and Leeds Assessment of Neuropathic Symptoms and Signs questionnaires. Sensory function was evaluated using the Semmes–Weinstein monofilament test. Statistical analysis was performed using paired t-tests. The mean Douleur Neuropathique-4 score decreased from 6.39 ± 1.38 to 5.13 ± 1.12 (p<0.001), and the mean Leeds Assessment of Neuropathic Symptoms and Signs score decreased from 16.45 ± 2.79 to 14.11 ± 2.86 (p<0.001). Significant improvement in tactile sensation was observed in selected peripheral nerves. Oral mekobalamin administered for three months significantly reduced neuropathic pain and improved peripheral sensory function, suggesting its potential role as adjunct therapy in leprosy neuropathy.